Knowledge Relationships And Family Attitudes In Dengue Hemorrhagic Fever Prevention Activities At Naioni - Yustinus Rindu; Agustina Ina (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Dengue Hemorrhagic Fever is an environment-based infectious disease that can cause death in a short time (Ministry of Health RI, 2011). Knowledge is the result of observing, hearing, feeling and thinking as a basis for making decisions to act in order to describe knowledge gained from experience. Knowing the relationship between knowledge, attitudes, and family beliefs in Dengue Hemorrhagic Fever prevention activities at the Naioni Health Center in Kupang City. In this study using the Case Study Method with a total sampling sample of 50 respondents The results showed that respondents' knowledge in dengue hemorrhagic fever prevention activities in the Good category was 18%, Enough 50%, Less 32%. While the attitude of respondents who were positive 42% and negative, 58% and respondents who were sure 30% and unsure 20%. Family knowledge in efforts to prevent dengue hemorrhagic fever is sufficient